Effect of Cerebral Small Vessel Disease Burden on Outcomes in Patients With Acute Ischemic Stroke Receiving Endovascular Treatment - Huang, Hao; Zong, Weifeng; Tong, Xu; Tian, Xue; Wang, Anxin; Jia, Baixue; Zhao, Jing; Wu, Lingshan; Zhou, Xirui; Guo, Yinping; Zhang, Yi; Yu, Zhiyuan; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Cerebral small vessel disease (SVD) is common in the aging population. The study aimed to evaluate the effect of SVD on functional outcomes in patients with acute ischemic stroke (AIS) receiving endovascular treatment (EVT). Methods: From a prospective registry, we selected patients with AIS receiving EVT. SVD features, including white matter hyperintensities (WMH), lacunes and brain atrophy, were assessed on MRI and a validated SVD score was calculated to reflect the total SVD burden. Results: Among 137 patients included, 106 had none-mild SVD burden and 31 had moderate-severe SVD burden. The moderate-severe SVD burden group showed a significantly higher modified Rankin Scale score at 90 d (median, 4 versus 1 points, adjusted common odds ratio 0.32 [95% CI, 0.14–0.69], P < 0.01) and a significantly smaller improvement of NIHSS at 24 h (median, -3 versus -3 points, adjusted β coefficient 4.02 [95% CI, 0.57–7.48], P = 0.02) and 7 d (median, -4 versus -6 points, adjusted β coefficient 4.71 [95% CI, 1.06–8.36], P = 0.01) than the none-mild group. There was no significant difference in successful recanalization, death within 90 d, symptomatic intracranial hemorrhage within 24 h between two groups (all P > 0.05). Additionally, for each single SVD feature, brain atrophy and WMH, but not lacunes, were associated with the functional outcome. Conclusion: Moderate-severe SVD burden was associated with poor early and late functional outcomes in patients with AIS receiving EVT. Our results suggest that SVD score may act as a good predictor of outcomes in these patients.